Ocular toxoplasmosis: background and evidence for an antibiotic prophylaxis - Reich, Michael; Mackensen, Friederike (Current opinion in ophthalmology, 2015)
Purpose of reviewThe purpose of this review was to provide an overview of current data on antibiotic prophylaxis in ocular toxoplasmosis.Recent findingsStudies showing the prophylactic effect of long-term antibiotics are discussed. Prophylaxis seems to be justified in patients with a high risk of re
Gesehen am 17.06.2020